Humanized attendance to pregnant: reality and challenges - Camila Almeida Silva, Luana Carla Lima de Almada, Zilma Nazaré Souza Pimental, Tayana de Sousa Neves, Tainã da Silva Lobato, Andréa Reni Mendes Mardock (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.7310-16